Microbiological quality, proximate composition and in vitro starch/protein digestibility of Sorghum bicolor flour fermented with lactic acid bacteria consortia - Alloysius Chibuike Ogodo; Ositadinma Chinyere Ugbogu; Reginald Azu Onyeagba; Hope Chukwuemeka Okereke (Chemical and Biological Technologies in Agriculture, 2019)
Abstract Background This study evaluated the effect of lactic acid bacteria (LAB) consortium fermentation on proximate and in vitro starch and protein digestibility of sorghum flour using standard techniques at 12-h intervals. Lactic acid bacteria previously isolated from fermenting maize and sorghum were combined as follows: Lactobacillus nantensis LP33 + Lactobacillus plantarum WCFS1 + Lactobacillus fermentum CIP102980 + Lactobacillus rhamnosus GG ATCC53/03 + Lactobacillus reuteri DSM20016 and Lactobacillus fermentum CIP102980 + Lactobacillus brevis ATCC14869 + Lactobacillus nantensis LP33 + Pediococcus acidilactici DSM20284 + Lactobacillus plantarum WCFS1 for consortium from maize and sorghum, respectively, and used to ferment sorghum flour. The flour was also fermented spontaneously for comparison. Results The result showed significant (p < 0.05) increase in moisture, ash and protein contents; while fiber, lipid and carbohydrate contents decreased with increasing fermentation time in all set-ups. The in vitro protein digestibility increased significantly (p < 0.05) from 63.68 ± 1.46 to 79.89 ± 1.14%, 63.68 ± 1.46 to 83.72 ± 2.08% and 63.68 ± 1.46 to 84.28 ± 2.16% for naturally, LAB consortium from maize-fermented and LAB consortium from sorghum-fermented samples, respectively. Total viable count and total lactic acid bacteria count increased with fermentation with no coliform and fungal count in the consortia-fermented sample. The occurrence of isolates showed that only starter organisms were isolated from the consortia fermentations. Conclusion This study has shown the effectiveness of LAB consortium fermentation in improving the nutritional quality and in vitro starch/protein digestibility of sorghum flour which holds potential in food fortification by food industries.